2020
DOI: 10.3390/ijerph17228466
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Animal-Assisted Therapy on Episodic Memory in Patients with Acquired Brain Injuries

Abstract: Animal-assisted therapy (AAT) is shown to be an effective method to foster neurorehabilitation. However, no studies investigate long-term effects of AAT in patients with acquired brain injuries. Therefore, the aim of this pilot study was to investigate if and how AAT affects long-term episodic memory using a mixed-method approach. Eight patients rated pictures of therapy sessions with and without animals that they attended two years ago. Wilcoxon tests calculated differences in patients’ memory and experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Changes in mood after AAT can have an effect on depression and rehabilitation motivation due to the positive emotions generated in patients while enjoying spending time with the animal [40,41]. These findings are consistent with previous studies showing that AAT improves patients' post-stroke memory [39], patient participation [20], and mood [18]. As a result, AAT can be seen as boosting rehabilitation motivation and decreasing depressive symptoms, because the therapeutic atmosphere is light, stress is low, and the activity itself (dog walking) incites pleasure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Changes in mood after AAT can have an effect on depression and rehabilitation motivation due to the positive emotions generated in patients while enjoying spending time with the animal [40,41]. These findings are consistent with previous studies showing that AAT improves patients' post-stroke memory [39], patient participation [20], and mood [18]. As a result, AAT can be seen as boosting rehabilitation motivation and decreasing depressive symptoms, because the therapeutic atmosphere is light, stress is low, and the activity itself (dog walking) incites pleasure.…”
Section: Discussionsupporting
confidence: 91%
“…Post-stroke patients often have difficulty during rehabilitation due to negative emotions such as depression [6,7]. However, Theis et al (2020) showed that AAT triggers positive emotions and low levels of arousal in patients with acquired brain injury [39]. Changes in mood after AAT can have an effect on depression and rehabilitation motivation due to the positive emotions generated in patients while enjoying spending time with the animal [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…An animal-assisted mindfulness intervention for patients with recurrent depression was found to lead to a decrease in depressive symptoms and rumination, and an improvement in overall mindfulness skills with no dropouts 35 . Other studies indicate positive effects of interacting with animals on social behavior and motivation 36 , 37 , mood 38 , establishing contact, communication and relaxation 39 , stress-related parameters and positive emotional-physiologic states 40 , anxiety 41 , 42 , episodic memory 43 , concentration 44 , 45 , and engagement in behavioral and mental health services 34 . Integrating a domesticated animal in a psychotherapeutic intervention, delivered by a psychotherapist with additional certification in animal-assisted therapy, is conceptualized as animal-assisted psychotherapy 46 , 47 .…”
Section: Introductionmentioning
confidence: 99%